Overview of nanoscale NEXAFS performed with soft X-ray microscopes - Guttmann, Peter; Bittencourt, Carla (Beilstein Journal of Nanotechnology, 2015)
Today, in material science nanoscale structures are becoming more and more important. Not only for the further miniaturization of semiconductor devices like carbon nanotube based transistors, but also for newly developed efficient energy storage devices, gas sensors or catalytic systems nanoscale and functionalized materials have to be analysed. Therefore, analytical tools like near-edge X-ray absorption fine structure (NEXAFS) spectroscopy has to be applied on single nanostructures. Scanning transmission X-ray microscopes (STXM) as well as full-field transmission X-ray microscopes (TXM) allow the required spatial resolution to study individual nanostructures. In the soft X-ray energy range only STXM was used so far for NEXAFS studies. Due to its unique setup, the TXM operated by the Helmholtz-Zentrum Berlin (HZB) at the electron storage ring BESSY II is the first one in the soft X-ray range which can be used for NEXAFS spectroscopy studies which will be shown in this review. Here we will give an overview of the different microscopes used for NEXAFS studies and describe their advantages and disadvantages for different samples.
Keywords: NEXAFS; STXM; TXM; X-ray microscopy